Motivation factors affecting project manager’s job performance in Malaysia and Singapore / Ng Zhe Xhiang - Ng , Zhe Xhiang (2024)
The construction industry significantly contributes to a country's economic sector, relying heavily on the job performance of its project members. However, the construction industry in Malaysia and Singapore still faces room for improvement in job performance. Researchers have identified failures in achieving time, cost, and quality goals in numerous construction projects in these countries are mainly due to lack of motivation practice in the industry. Thus, the aim of this study is to explore suitable motivation practices that can enhance the job performance of project managers (PMs) in Malaysia and Singapore. A literature review was conducted by studying previous research articles, journals, and books concerning motivation and job performance. This study adopted a quantitative approach, sending out 256 sets of questionnaire surveys to project managers in Malaysia and Singapore through email. However, only 33.6% received responses. Collected data was analysis using mean analysis to determine the motivation factors affecting job performance, strategies to improve job performance, and the performance of PMs' roles. High salary levels, fringe benefits, and job safety were ranked as the top three motivation factors. Next, the Mann-Whitney U test was used to determine significant differences in agreement levels on motivation factors and job performance. Subsequently, Pearson’s correlation test was conducted to identify the correlation between motivation factors and job performance. It was found that most of the motivation factors has positive correlation with the role of project manager. This research is beneficial to PMs and other construction stakeholders in Malaysia and Singapore. By instilling motivation in employees, it is possible to improve the job performance of individuals.